USING CARD-SORT METHOD IN EFL WRITING CLASSROOM - Subroto, Gatot (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research was aimed at knowing the effectiveness of the card-sort method in teaching EFL writing. The writing was focused on descriptive text. The researchers used two groups of pre-test post-test experimental research design. The subject of this research was the eighth-grade students of SMP Negeri 24 Bintan. In this research, the researchers chose two classes, experimental and control classes, consist of 34 students by applying the purposive sampling technique. Writing test was used to gather the data needed. Based on the result of the statistic calculation, the result of the pre-test of the experimental class was 49 and the control class was 54 while the result of post-test was 70 for the experimental class and 64 for the control class. The tcount was 4.881 with significant level 0.05. Based on the data analysis, the researchers concluded that sig 0.000 < 0.05 which meant there was the effect of the card-sort method in teaching EFL writing.